rozwiąż równanie 3×^+×+7=0 ×^-6×+9=0 ×^-×-6=0 3×^+7×+2=0​



Odpowiedź :

1]

[tex]3x^2+x+7=0\\\\a=3, \ b=1, \ c=7\\\\\Delta=1^2-4\cdot3\cdot7=1-84=-83<0[/tex]

Brak rozwiązań

2]

[tex]x^2-6x+9=0\\\\(x-3)^2=0\\\\x-3=0\\\\x=3[/tex]

3]

[tex]x^2-x-6=0\\\\a=1, \ b=-1, \ c=-6\\\\\Delta=(-1)^2-4\cdot1\cdot(-6)=1+24=25\\\\\sqrt{\Delta}=\sqrt{25}=5\\\\x_1=\frac{-(-1)-5}{2\cdot1}=\frac{-4}{2}=-2\\\\x_2=\frac{-(-1)+5}{2\cdot1}=\frac{6}{2}=3[/tex]

4]

[tex]3x^2+7x+2=0\\\\a=3, \ b=7, \ c=2\\\\\Delta=7^2-4\cdot3\cdot2=49-24=25\\\\\sqrt{\Delta}=\sqrt{25}=5\\\\x_1=\frac{-7-5}{2\cdot3}=\frac{-12}{6}=-2\\\\x_2=\frac{-7+5}{2\cdot3}=\frac{-2}{6}=-\frac{1}{3}[/tex]